The Development Model of Tourist Souvenirs Based on Cultural Structure - Ke Lu, Liying Wei, Xinyang Zhang (Forest Chemicals Review, 1970)
There is still a lack of sufficient scientific understanding and theoretical research on the essential characteristics, value characteristics, and origins of tourist souvenirs. This paper adopts the speculative research method and based on the theoretical thought of cultural structure, points out that tourist souvenirs constitute their core value characteristics by distinguishing, remembering, and publicizing, corresponding to the cultural roots of their value characteristics formed by material culture, institutional culture, and spiritual culture, and points out The cultural depiction of tourist destinations is the essential feature of tourist souvenirs; further, the pattern analysis method is used to construct the cultural structure model of tourist souvenir development, and it is pointed out that the systematic mining and utilization of different structural elements of regional culture is the core idea of tourist souvenir development. The development framework below includes focusing on innovative utilization and reflection of regional material culture, emphasizing authenticity and restoring or expressing regional institutional culture, and focusing on presenting and disseminating regional spiritual culture. This research provides a theoretical basis for the research and a reference for the practice of regional cultural tourist souvenirs development.